EFEK HEPATOPROTEKTOR INFUSA DAUN BINAHONG (ANREDERA CORDIFOLIA) TERHADAP SGOT DAN SGPT TIKUS TERINDUKSI PARASETAMOL: Hepatoprotective Effect Of Binahong (Anredera Cordifolia) Leaf Infusion On SGOT And SGPT Levels In Paracetamol-Induced Rats - Novita Sari; Salsa Azzahrany Suseno; Akbar R Saputra (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
A hepatoprotector is a compound that can protect the liver from damage caused by toxic substances and facilitates the repair of liver tissue. Liver damage can be indicated by increased elevated levels of the enzymes SGOT (Serum Glutamic Oxaloacetic Transaminase) and SGPT (Serum Glutamic Pyruvic Transaminase). Binahong leaves (Anredera cordifolia) contain flavonoid compounds that have potential as hepatoprotective agents. This study aimed to evaluate the activity of binahong leaf infusion on SGOT and SGPT levels in white rats induced with paracetamol. This was an experimental study using a post-test group design involving 25 rats divided into five groups: a negative control group (0.5% CMC), a positive control group (Hepamax at a dose of 11.81 mg/200 g BW), and treatment groups I, II, and III, which received binahong leaf infusion at doses of 100 mg/200 g BW, 200 mg/200 g BW, and 300 mg/200 g BW, respectively, for 7 days orally. Subsequently, all groups were induced with paracetamol at a dose of 270 mg/200 g BW for 1 day. Analysis of SGOT and SGPT levels using One-way Analysis of Variance (ANOVA) followed by Duncan’s test. The results showed that administration of binahong leaf infusion at 300 mg/200 g BW (Group III) produced the most significant reduction in liver enzyme levels. The average SGPT level in Group III was 63.2 U/L, and SGOT was 26.4 U/L. These results were statistically significantly different compared to the negative control group (p < 0.05) and demonstrated effectiveness approaching that of the positive control (Hepamax). Keywords: Anredera cordifolia, Binahong leaves, Hepatoprotector, Paracetamol, SGOT, SGPT